Laser and light-based therapy for hair growth and hair removal - Wiryadana, Michelle; Jusuf, Nelva Karmila (UI Scholars Hub, 2025)
Background: Recent advances in laser and light-based technologies have introduced new options for both the stimulation of hair growth for alopecia and the reduction of unwanted hair growth. However, the clinical evidence remains varied, and treatment outcomes are influenced by factors such as device type, wavelength, and individual response. Ongoing evaluation of safety, efficacy, and standardization of treatment parameters is therefore essential. Discussion: This review provides an in-depth discussion of the principles, mechanisms, safety, and efficacy of lasers in promoting hair growth, as well as on lasers and light-based therapies used for hair removal. The mechanisms of laser-induced hair growth stimulation include the acceleration of vellus hair transformation into terminal hair. In contrast, lasers and light-based devices utilize melanin as a target chromophore for hair removal. Conclusion: Appropriate devices and techniques of lasers and light-based devices, whether used alone or in combination with other therapies, are beneficial for both hair growth and hair removal.